Computational fluid dynamics (CFD) study of patients suffering coarctation of the aorta (CoA) for pre and post-operative - abozaid, omar (AUC Knowledge Fountain, 2016)
Coarctation of the aorta (CoA) is a widespread anomaly that occurs a lot in infants. CoA affects the human health. It causes hypertension, decrease in the amount of blood flow and heart failure. CoA is related to abnormal hemodynamics and certain blood flow patterns are noticed. Different surgical techniques are implemented in order to increase the amount of blood flow such resection end-to-end anastomosis, resection end-to-side anastomosis…etc. This research aims at identifying the effect of CoA on the flow pattern and quantification of the improvement after surgery through utilizing computational fluid dynamics (CFD) to solve flow fields in the aorta. CFD is applied on a real geometry of the aorta are obtained by computerized tomography (CT) scan for five pre and post-operative patients. The boundary conditions are derived from the phase contrast magnetic resonance imaging (PC-MRI). Then, grid independence and time sensitivity analysis are performed. Flow patterns are judged visually by comparing the contours of the streamlines, vortex core, pressure and the time averaged wall shear stress (TAWSS). In order to quantify the flow fields and the improvement as well, different flow variables are used such as Womersley number, Strouhal number and specific turbulent kinetic energy. The wall shear stress at peak systole and the amount of the blood flow in the direction of the vessel’s centerline are used as a measure of improvement. The results of the CFD showed that blood flow patterns are highly dependent on the geometry of the vessel. For a CoA, jet formulation then break up, backflow and chaotic behavior exists after the area of the disease. In addition, a high concentrated wall shear stress is around the area of the CoA. For post-op, the change of the area because of the surgery produced separation. For both pre and post-op, the angle between the velocity vector at the inlet and the centerline of the vessel resulted in a jet impingement and very high wall shear stress. On the other hand, the specific turbulence kinetic energy and the wall shear stress is higher after the surgery. Strouhal number in the descending aorta has decreased after the operation except for one patient. The amount of blood flow increased after the surgery. Blood flow in the downstream became attached to the vessel. Finally, the flow fields are sensitive to the turbulence model; however, they did not show significant dependence on the viscosity model. The turbulence effects cannot be neglected due to their significant contribution to the velocity field.